Pemberdayaan Masyarakat dalam Pengelolaan Sampah Rumah Tangga Berbasis Bank Sampah melalui pendekatan lingkungan Bersih dan Sehat di Desa Jatirejo, Kabupaten Madiun - Hidayati, Nasrul Rofiah; Sudarni, Dyan Hatining Ayu; Sunaryantiningsih, Ina; Kiswardianta, R. Bekti (CV. ITTC INDONESIA, 2026)
The problem of household waste remains a major challenge in realizing a clean and healthy environment, especially in rural areas. Jatirejo Village, Madiun Regency, faces increasing household waste generation that has not been optimally managed due to a lack of public awareness and limitations in the integrated waste management system. This activity aims to empower the community in waste bank-based household waste management through a clean and healthy environment approach. The implementation method includes socialization and education about waste sorting, waste bank management training, operational assistance, and monitoring and evaluation of community participation. The results of the activity show an increase in public knowledge and awareness of the importance of waste management, increased household participation in waste sorting, and the establishment of a waste bank system that functions as a means of managing economically valuable waste. This program also contributes to efforts to reduce the burden of waste and create a cleaner, healthier, and more sustainable environment.